Enhancing the thermoelectric properties of SnTe via introducing PbTe@C core–shell nanostructures. Issue 30 (14th July 2021) - Zhang, Jingwen; Li, Song; Zhu, Zhengyi; Wu, Zhenwang; Zhang, Jiuxing
Abstract : Introducing 5 wt% amorphous carbon core–shell-coated PbTe nanoparticles in SnTe-based TE materials increases the ZT by approximately 30.3%. Abstract : SnTe is an emerging IV–VI metal chalcogenide, but its low Seebeck coefficient and high thermal conductivity mainly originating from the high hole concentration limit its thermoelectric performance. In this work, an amorphous carbon core–shell-coated PbTe nanostructure prepared by a "bottom-up" method is first incorporated into the Sn1− y Sb y Te matrix to enhance the thermoelectric performance of SnTe. The square-like PbTe nanoparticles maintain their original cubic morphology and do not grow up obviously after the SPS process due to the coating of the C layer, bringing about the formation of nanopores locally, while Sb alloying induces Sb point defects and Sb-rich precipitates. All these unique hierarchical microstructures finally lead to an ultralow lattice thermal conductivity (∼0.48 W −1 m −1 K −1 ) approaching amorphous limits (∼0.40 W −1 m −1 K −1 ). In addition, the incorporation of PbTe@C core–shell nanostructures decreases the carrier mobility obviously with a slight loss in carrier concentration, resulting in the deterioration of electrical properties to a certain extent. As a result, a peak thermoelectric figure of merit ( ZT ) of 1.07 is achieved for Sn0.89 Sb0.11 Te-5%PbTe@C at 873 K, which is approximately 154.76% higher than that of pristine SnTe. This work provides a new strategy to enhance the thermoelectric performance of SnTe and also offers a new insight into other related thermoelectric systems.